The Effect of Teaching Strategies and Students Curiosity on Students’ Achievement in Reading Comprehension - Fitri Ervina Tarigan, Ika Vanesia Siagian, Badriyyah Jamil, Ahmad Rozik (Pusdikra Publishing, 2021)
The objective of this research was to investigate whether: (1) The students’ achievement in reading comprehension taught by using INSERT strategy was higher than that taught by using K-W-L strategy, (2) The students’ achievement in reading comprehension with high curiosity was higher than that low curiosity, and (3) There was interaction between teaching strategies and curiosity on the students’ achievement in reading comprehension. This study was conducted at SMP Al-Ulum Medan during academic year 2017/2018. The population of this study was the eighth grade student which consists of six classes namely VIII-1, VIII-2, VIII-3, VIII-4, VIII-5, and VIII-6. So, the total of population was 228 students. Then two classes of grade VIII-4 and VIII-6 were chosen in this study as the sample. This study was an experimental research. The instrument used in this research was reading comprehension test and questionnaire sheet. The data were analysed by using two ways analysis of variance (Anova) 2x2 factorial design F-test at the level of significant 5% or ? = 0.05. The result of data analysis proved that: The students’ achievement in reading comprehension taught by using INSERT strategy was higher than that taught by using K-W-L strategy, (2) The students’ achievement in reading comprehension with high curiosity was higher than that low curiosity, and (3) There was interaction between teaching strategies and curiosity on the students’ achievement in reading comprehension by observing the data analysis, and the scores means of the students.